Democracy erodes from the top : leaders, citizens, and the challenge of populism in Europe - Bartels, Larry M., 1956- 1956- (Princeton studies in political behavior, 2023)
"There is a palpable sense of crisis in Western democracies. The rise of right-wing populist parties across Europe, the erosion of constitutional checks and balances in Hungary and Poland, and the 2016 Brexit vote in the UK have all stirred significant alarm regarding the present state of democracy and prospects for its future. And political leaders and would-be leaders have not hesitated to stoke perceptions of crisis in pursuit of their own ends. However, on the whole, Europeans in 2019 were just as satisfied with the working of democracy as they had been 15 years earlier. Trust in national parliaments and politicians remained virtually unchanged. While "angry opponents of immigration" dominated the headlines, most Europeans' attitudes toward immigration were becoming significantly warmer, not more hostile. In these and other respects, the conventional wisdom about a "crisis of democracy" in contemporary Europe is strikingly at odds with evidence from public opinion surveys. Drawing from a major survey of European public opinion, Bartels summarizes broad trends from 2002 through 2019, focusing on attitudes commonly taken as symptomatic of a "crisis of democracy," including dissatisfaction with the workings of democracy, distrust of political elites, ideological polarization, and antipathy to European integration. He finds, with remarkable consistency across issues, that the European public does not see their democracy as in crisis. Bartels then goes on to show how these findings complicate the sense, for instance, that the surge in support for right-wing populist parties is driven by a "demand" for such groups from the public. Rather, this and other troubling changes has much more to do with the "supply" of groups within the political elite. It is these elite groups, Bartels ultimately finds, that have contributed to the erosion of democratic norms and institutions in places like Poland and Hungary-not an increasingly restive European public"--